Prevalence, Risk Factors, Harm Perception, and Attitudes Toward E-cigarette Use Among University Students in Qatar: A Cross-Sectional Study - Kurdi, Rana; Al-Jayyousi, Ghadir Fakhri; Yaseen, Manar; Ali, Aatefeh; Mosleh, Neama; Abdul Rahim, Hanan F. (Frontiers in Public Health, 2021)
Background: Electronic cigarette (e-cigarette) use is becoming more popular worldwide, especially among youth. Studies report that university students have inadequate knowledge as well as misconceptions about the health risks of e-cigarettes, which may lead to their use even in populations where smoking prevalence is relatively low. At this age, the influence of peers is also significant. Understanding attitudes of university students toward the use of e-cigarettes is important for effective tobacco prevention interventions. In this study, we assess the prevalence of e-cigarette use among students in Qatar's largest national university, as well as their knowledge, attitudes, and perceptions of harm in relation to e-cigarettes. Methodology: We conducted a cross-sectional study among Qatar University students using a self-administered online questionnaire. Descriptive univariate analyses were conducted as well as bivariate analyses to check the association of e-cigarette use with variables of interest. A binary logistic regression analysis was conducted to assess determinants of e-cigarette use among students. Results: One hundred ninety-nine students completed the questionnaire. The prevalence of e-cigarette use among students was 14%, with no significant difference by gender (16.2% in males and 12.8% in females). In bivariate analyses, significantly fewer e-cigarette users believed that e-cigarettes cause disease compared to non-users. 67.9% of e-cigarette users compared to 37.6% of non-users believed that e-cigarettes were less harmful than traditional cigarettes, and 78.6% of users compared to 40.4% of non-users believed that their use could be helpful in preventing smoking traditional cigarettes. Bivariate associations between e-cigarette use and knowledge items were significant (p < 0.05) as well as having a smoker among siblings or friends. In the multivariate analysis, only having a friend who was a smoker remained significant after controlling for other variables (OR = 7.3, p < 0.001). Conclusion: Our study found that university students have knowledge gaps and misconceptions with regard to the harms associated with e-cigarettes use, especially among users. A comprehensive smoking prevention policy, educational interventions, and quit support are needed to enhance awareness among university students about the health effects associated with e-cigarettes use. Such interventions should also take into account the influence of peers on smoking practices.